2021
DOI: 10.1021/acs.jpcb.1c08383
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulations of Aqueous Electrolytes: Role of Explicit Inclusion of Charge Transfer into Force Fields

Abstract: We describe here simulations of aqueous salt solutions that are performed using an explicit charge transfer force field. The emphasis of the discussion is on the calculation of a dynamical property of the solutions: selfdiffusion of water. While force fields that are based on pairwise additive potentials or on potentials with explicit inclusion of polarization or with scaled charges can provide at best a qualitative agreement with experiments, force fields with explicit inclusion of charge transfer can produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…20 Classical forcefields were shown to lead to a retardation of water dynamics for all investigated cations, including Cs + , [19][20][21] which therefore contrasts with the acceleration that has been measured by several techniques for this dilute cation. This has led to the suggestion that DFT-based MD 21 or simulations accounting for charge transfer 22 are required. However, another promising approach relies on scaled ion charges, 23,24 that implicitly account for the fast electronic dielectric response of water.…”
Section: Simulation Strategy and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Classical forcefields were shown to lead to a retardation of water dynamics for all investigated cations, including Cs + , [19][20][21] which therefore contrasts with the acceleration that has been measured by several techniques for this dilute cation. This has led to the suggestion that DFT-based MD 21 or simulations accounting for charge transfer 22 are required. However, another promising approach relies on scaled ion charges, 23,24 that implicitly account for the fast electronic dielectric response of water.…”
Section: Simulation Strategy and Modelsmentioning
confidence: 99%
“…We use molecular dynamics simulations which have already been successfully employed to elucidate how anions affect water reorientation dynamics. 7,8,14,15 However, for cations, traditional classical forcefields have been shown to fail to reproduce the experimentally observed acceleration of water dynamics induced by some large cations, [19][20][21] and it has been suggested that density functional theory(DFT)-based simulations 21 or simula-tions explicitly accounting for cation-water charge transfer 22 are required. Here we performed both DFT-based simulations and classical non-polarizable simulations with a rescaled-cation charge (ECC) approach.…”
Section: Introductionmentioning
confidence: 99%
“…126 Further reparameterization of polarizable FFs to improve agreement presents a major challenge as the slow dynamics of DESs necessitates in impractically long time lengths to achieve statistically accurate results. 124 New methods or approaches, perhaps encompassing machine learning or FFs with explicit inclusion of charge transfer, 149,150 will be required to achieve accurate self-diffusivity reproduction and prediction for DESs. As one considers the potential for dramatic computational advances over the next 25 years, it is not difficult to imagine a day when FFs could be completely replaced with low-cost QM methods, particularly for solvent systems such as DESs.…”
Section: Self-diffusion Coefficientsmentioning
confidence: 99%
“…We note that considering the charged system without a counter ion implicitly assumes a model for a diluted solution/interface. From prior work with charged species in the literature such an approach is warranted if one takes into account the effects of the polarization of the solvent 86,[89][90][91][92][93][94] , and has been shown to yield spectroscopic results 62,95 that closely match experimental measurements, provided of course the model mirrors the essential features of the experimental system.…”
Section: B Md-derived Structuresmentioning
confidence: 99%